PENGARUH ROE TERHADAP NILAI PERUSAHAAN DENGAN STRUKTUR MODAL SEBAGAI VARIABEL MODERATING (SUB SEKTOR MAKANAN MINUMAN TAHUN 2016-2018) - virolita, nadia (Jurnal Ekonomi : Journal of Economic, 2020)
One basis for investor decision making to invest is to look at a company's financial performance. Financial performance that affects the value of a company. One financial performance is profitability and capital structure. This study aims to determine how much the value of the company is influenced by profitability (ROE) with a capital structure as a moderating factor. Measurement of company value using Tobin's Q. The results of this study profitability (ROE) has a positive effect on firm value. However, the capital structure (DER) cannot moderate the profitability relationship (ROE) to the value of the company, especially in the food and beverage sub-sector listed on the Stock Exchange in 2016-2018Keyword : ROE, DER, Firm Value